2007
DOI: 10.1200/jco.2006.07.9525
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib Plus Gemcitabine Compared With Gemcitabine Alone in Patients With Advanced Pancreatic Cancer: A Phase III Trial of the National Cancer Institute of Canada Clinical Trials Group

Abstract: To our knowledge, this randomized phase III trial is the first to demonstrate statistically significantly improved survival in advanced pancreatic cancer by adding any agent to gemcitabine. The recommended dose of erlotinib with gemcitabine for this indication is 100 mg/d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

61
2,401
9
64

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 3,452 publications
(2,535 citation statements)
references
References 33 publications
61
2,401
9
64
Order By: Relevance
“…Recent advances in the clinical management of this disease, especially new chemotherapeautic reagents, such as gemcitabine (Burris et al, 1997), have improved patient outcome. In addition, recent progress in molecular cancer biology has led to the development of new molecular targeting therapies for pancreatic cancer; some of these new drugs, such as erlotinib, an epidermal growth factor receptor inhibitor (Moore et al, 2007), have already shown clinical benefits. However, the efficacy of these new therapies has not been sufficient enough, with only a few months' improvement in median survival time, and additional molecular targets are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in the clinical management of this disease, especially new chemotherapeautic reagents, such as gemcitabine (Burris et al, 1997), have improved patient outcome. In addition, recent progress in molecular cancer biology has led to the development of new molecular targeting therapies for pancreatic cancer; some of these new drugs, such as erlotinib, an epidermal growth factor receptor inhibitor (Moore et al, 2007), have already shown clinical benefits. However, the efficacy of these new therapies has not been sufficient enough, with only a few months' improvement in median survival time, and additional molecular targets are urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Both of which showed an improved efficacy with gemcitabine/capecitabine combination with the UK study showing statistically superior survival advantage over gemcitabine alone (P ¼ 0.026) . However, more recently, erlotinib, an epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, plus gemcitabine has also been reported to improve survival over gemcitabine alone (Moore et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Only erlotinib, an inhibitor of the epidermal growth factor receptor and recently (September 2013) Abraxane (paclitaxel albumin-bound nanoparticles) have been approved by the FDA in combination with gemcitabine due to the significant improvement in patient survival and delay in tumor growth [5][6][7]. Due to its rather hydrophilic character, gemcitabine is unable to passively diffuse across the plasma membrane but it is transported into the cell by either human equilibrative (hENT) or sodiumgradient nucleoside transporters.…”
Section: Introductionmentioning
confidence: 99%